IMPLEMENTASI KEPEMIMPINAN PEMBELEJARAN UNTUK MEWUJUDKAN MUTU SEKOLAH - Danang Nugroho; Afifah Novianti; Ahmad Luthfi alfian; Erdi Supandi; Muhamad Ainul Reza; Novia Febrianty (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Due to time constraints and limited guidance, there remains room for improvement in students' academic performance. To address this issue, the principal and school staff coordinate extracurricular activities as an additional strategy to enhance academic success and foster students' talents and interests. These extracurricular endeavors, conducted outside regular class hours, serve not only as a means for the principal to support learning but also as avenues for enhancing the overall educational experience. In this study, literature review methods are employed to identify theories relevant to contemporary leadership phenomena. The theoretical frameworks uncovered in this research will serve as the foundation and roadmap for subsequent field investigations. Literature review, a method used to gather pertinent information and sources, spans across various media platforms. The findings underscore the critical role of effective learning management within the school setting. The principal collaborates with all stakeholders to improve the learning environment. Emphasizing the importance of extracurricular activities in enriching the learning process, efforts are directed towards enhancing school quality. Leadership in education serves as the cornerstone in aligning all activities with the school's vision, mission, and objectives. By fostering a secure and enjoyable learning atmosphere, the principal inspires enthusiasm and enjoyment in the educational journey. Despite diligent educational initiatives, there remains potential for further enhancing the academic achievements of all students